Physical and biological properties of a novel anti-adhesive punctate uneven gelatin film. - Yuki Ozamoto; Tsunehito Horii; Shinichiro Morita; Hiroyuki Tsujimoto; Yasumitsu Oe; Hiroshi Minato; Joe Ueda; Hiroshi Ichikawa; Akihiro Kawauchi; Akeo Hagiwara; Susumu Kageyama; Masaji Tani (PLoS ONE)
Since abdominal adhesion are quite problematic in abdominal and pelvic surgery, the conventional HA/CMC film are commonly used as an anti-adhesive material. However, such types are difficult to be rolled and delivered through the port of laparoscopic surgical devices due to adherence to the laparoscopic port or other parts of the films. To create an anti-adhesion film with more favorable handling properties and anti-adhesive effect, we developed a novel punctate uneven gelatin film (PU GF). In this study, we examined the physical strength, flexibilities and adhesiveness between film to tissues or film each other, compared to the conventional film and the flat gelatin film (Flat GF). In addition, we investigated the cell proliferation on each film and the anti-adhesive effect of the films and those reattachment possibility using a rat cecum abrasion model. The PU GF showed excellent tensile strength, ductility, and adherence to tissue compared to Flat GF and the conventional film. Moreover, the adherence of PU GF to the other film and to a silicon sheet were much lower than those of the Flat GF and conventional film. The proliferation of cells in PU GF and Flat GF were suppressed compared with control, though increased with time. The anti-adhesive scores of the PU GF after one time and re-attachment were significantly higher than that of non-covered control, although there was no significant difference between that of the conventional film and control. Our findings suggest that PU GF improve handling properties of laparoscopic surgery as it has excellent physical strength, ductility, and adherence to tissue, and low adherence to trocar. In addition, the punctate film may be more useful with the re-attachability without tearing and to retained sufficient anti-adhesion effect.